Selectively Self-Aligned Sol-Gel Copper Oxide for Large-Area Multi-Valued Logic Devices - Baek, Seokhyeon; Kim, Wonsik; Lee, Won June; Choi, Jun Gyu; Park, Sungjun (Small, 2024)
Rapid expansion of digital information density has led to a growing demand for multi-valued logic (MVL) systems, which aim to minimize energy and time consumption for computations. Heterojunction transistors represent a class of device architectures for MVL circuits; however, partially layered structures can be realized only for vacuum-deposited organic and transferred 2D materials due to the constraints of patterning processes. In this study, a novel CuxO/IGZO heterojunction-based ternary inverter is presented via a sol-gel technique and direct patterning process using a self-assembled monolayer (SAM). This approach allows for a promising alternative to conventional photolithography, with the electrical characteristics of SAM-processed oxide thin-film transistors closely matching those of pristine devices. Structural investigations validate the partially overlapped heterojunction and its smoothness. Depth profiling with x-ray photoelectronspectroscopy highlights an oxidation gradient in CuxO, suggesting enhanced hole introduction at the IGZO interface. This mechanism potentially supports efficient hole transport and negative differential transconductance, foundational for MVL systems. Such advancements signify the potential for solution-processable digital electronics that offer streamlined fabrication at an affordable budget.
Keywords: Direct-patterning; Heterojunction transistors; Logic systems; Metal-oxide; Multi-valued; Multi-valued logic device; Oxide heterojunction transistor; Oxide transistors; Sol'gel; Sol-gel metal oxide transistor; direct patterning; multi-valued logic device; oxide heterojunction transistor; self-assembled monolayer; sol-gel metal oxide transistor